Assessment of economic threshold concepts in higher education. (January 2019) - Tang, Tommy
Abstract: Economics educators generally agree that opportunity cost and price mechanism are economic threshold concepts. If we assess students' higher order thinking in the academic context, we would expect a strong association between students' demonstrated ability of applying threshold concepts in real life context and their academic achievement. In this interview study, no such association was observed. The paper argues that current economics education over-emphasises the acquisition of technical skills, at the expense of integrative understanding, resulting in the observed lack of real world relevance by economics students and contributing to the continuous decline in economics enrollment in Australian universities.